Body of lies [videorecording (DVD)] - Scott, Ridley; DiCaprio, Leonardo; Crowe, Russell, 1964-; Strong, Mark, 1963-; Ignatius, David, 1950- (Warner Home Video, 2009)
CIA operative Roger Ferris is on a covert mission. He is working in Jordan and searching for terrorists who have been bombing civilian targets. Ferris uncovers information on the Islamist mastermind Al-Saleem. He devises a plan to infiltrate Al-Saleem's terrorist network with the help of his Langley boss, Ed Hoffman. Ferris enlists the help of the Chief of Jordanian Intelligence, Hani Salaam on this operation, but what he is not certain of is how far he can trust him without putting his life in danger. The uneasy alliance leads to a cultural and moral clash between the men.